Property, patents, or people : 'what part of no don't you understand? - Reynolds, Paul (Universidad Nacional de Quilmes, 2002)
Maori and other indigenous people have always respected the sanctity and reciprocity of life. Patenting has no respect for life or the dignity for all life forms. There is no negotiation. In fact, there is a global chorusof people who say that patenting on life is non-negotiable. In the words of a Maori Anti-GE activist, "'What part of no don't you understand?' And that's how Maori spell it out. And people still ask questions so the next part of the question should be, 'What part of no don't you understand?'" My intention with this paper is to illuminate how and why patents have been made on life. The historical and genealogical construction of property has impacted on the creation of patents entitling the patent holder to private ownership of a life form. Myriad arguments will also be made as to why patenting on life is 'bad.' I will end with a selection of vibrant methods and ideas that I think are helpful in the recapturing of life.